Quantification of the openness of urban external space through urban section. Issue 4 (1st October 2020) - Tong, Ziyu; Yang, Huawu; Liu, Chen; Xu, Tingting; Xu, Sha
ABSTRACT: For the urban built environment, the shape characteristics of the external space are of decisive significance. However, what is commonly referred to as open space is more of a definition of social attributes. Therefore, in the research on urban environments, especially in urban microclimate, the study of a microclimate's correlation with open space easily produces deviations. The identification of the openness of an external space based on a direct quantitative description is an important prerequisite for the cognitive urban form. In this study, based on the height-to-width ratio (HWR) of different directional sections of external space, areas with high openness in an urban space are extracted by the threshold value. In the case analysis of different areas in Nanjing, China, the results showed that the method is effective and convenient. The results of the analysis can also be used more widely in the urban design and research.